Isomerization of lactose and lactulose production: review - Aider, Mohammed; Halleux, Damien de (Trends in food science & technology, 2007)
Lactulose is widely used in pharmaceutical, nutraceuticals and food industries because of its beneficial effects on human health. Technology of lactulose production is mainly based on the isomerization reaction of lactose in alkaline media. However, information available on this subject is very varied. This study is a summary of the principal techniques used for lactulose production in order to gather maximum information in one manuscript for a better comprehension of the technological characteristics and specificities of lactulose synthesis.